2020
DOI: 10.3390/su12031213
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of the Value of Timeless Design Styles for the Consumer Acceptance of Refurbished Products

Abstract: The prior use and age make refurbished products a less desirable option because they are perceived to be of lower quality, to have a reduced performance and a less attractive appearance. This research investigates one strategy on how to enhance the appearance of refurbished products and thereby encourage circular consumption via refurbishment. In 21 in-depth interviews, we explore whether embodying refurbished products in a timeless design can serve as a potential strategy to influence consumer acceptance of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…As suggested by Lobos [38], to achieve timelessness, designers could strive for simplicity by refraining from aesthetic cues that may indicate time markers such as particular trends. Another way to achieve timelessness can be by using a neo-retro design style [39]. Marc Newson's Ford 021c was described by the participant as "clearly from the future and past at the same time" (Figure 5a).…”
Section: Methodsmentioning
confidence: 99%
“…As suggested by Lobos [38], to achieve timelessness, designers could strive for simplicity by refraining from aesthetic cues that may indicate time markers such as particular trends. Another way to achieve timelessness can be by using a neo-retro design style [39]. Marc Newson's Ford 021c was described by the participant as "clearly from the future and past at the same time" (Figure 5a).…”
Section: Methodsmentioning
confidence: 99%
“…Studies [20,21] argued that products with a "simplistic design" retain their functional property over time, and hence postpone product obsolescence. As the same may apply to simplistic functions as well, we argue that studying the functional complexity of inherited products can provide insight into how and which functional properties can extend the lifetime of a product.…”
Section: Functional Propertiesmentioning
confidence: 99%
“…Page [7] found that a timeless design is very important regarding people's likelihood of keeping products. Further, Wallner et al [20] and Lobos [21] underlined the importance of a simplistic design (only very few ornaments and decorations) in extending a product's lifetime, since no fast trends affect aesthetics. Jordan [16] (p. 69) defined a timeless design as an honest design without unnecessary details.…”
Section: Invented Materials Plasticmentioning
confidence: 99%
See 1 more Smart Citation
“…On the emotional side, durability relates to enhancing user-object interactions and considering attachment over time (Baxter 2017). For example, the neo-retro and simplistic design styles were considered timeless by users in the case of refurbished products (which face the same durability issues than shared goods) by Wallner, Magnier, and Mugge (2020). If the criterion is not met, the object will be quickly deteriorated endangering the financial stability and the safety of the sharing system.…”
Section: 25/ Durabilitymentioning
confidence: 99%